Solid state 13C and 1H MAS NMR investigations of C60(ferrocene‒d10)2 complex. Issue 1 (2003) - Shabanova Shabanova, E. E.; Schaumburg Schaumburg, K. K.; Kamounah Kamounah, F. S. F. S.
Abstract : The article presents NMR investigations of a molecular crystalline material C60 (ferrocene‒d10 )2, which consists of two highly mobile molecules. 13 C and 1 H NMR line shapes and T1 relaxation times are discussed and compared with results obtained for the undeuteriated compound. The mobilities of C60 and ferrocene molecules were found to increase in the complex in comparison with the two components as crystalline materials.